Receptor-Mediated and Receptor-Independent Actions of Melatonin in Vertebrates - Hattori, Atsuhiko; Suzuki, Nobuo (Zoological science, 2024)
Melatonin ( -acetyl-5-methoxytryptamine) is an indolamine that is synthesized from tryptophan in the pineal glands of vertebrates through four enzymatic reactions. Melatonin is a quite unique bioactive substance, characterized by a combination of both receptor-mediated and receptor-independent actions, which promote the diverse effects of melatonin. One of the main functions of melatonin, via its membrane receptors, is to regulate the circadian or seasonal rhythm. In mammals, light information, which controls melatonin synthesis, is received in the eye, and transmitted to the pineal gland, via the suprachiasmatic nucleus, where the central clock is located. Alternatively, in many vertebrates other than mammals, the pineal gland cells, which are involved in melatonin synthesis and secretion and in the circadian clock, directly receive light. Recently, it has been reported that melatonin possesses several metabolic functions, which involve bone and glucose, in addition to regulating the circadian rhythm. Melatonin improves bone strength by inhibiting osteoclast activity. It is also known to maintain brain activity during sleep by increasing glucose uptake at night, in an insulin-independent manner. Moreover, as a non-receptor-mediated action, melatonin has antioxidant properties. Melatonin has been proven to be a potent free radical scavenger and a broad-spectrum antioxidant, even protecting organisms against radiation from space. Melatonin is a ubiquitously distributed molecule and is found in bacteria, unicellular organisms, fungi, and plants. It is hypothesized that melatonin initially functioned as an antioxidant, then, in vertebrates, it combined this role with the ability to regulate rhythm and metabolism, via its receptors.